A microfluidic detection system for quantitation of copper incorporating a wavelength-ratiometric fluorescent quantum dot pair. Issue 7 (8th February 2017) - Pengpumkiat, Sumate; Wu, Yuanyuan; Boonloed, Anukul; Bandara, Gayan C.; Remcho, Vincent T.
Abstract : Described is a new approach to building a microfluidic quantum dot wavelength-ratiometric sensor system for quantifying copper in water and biological samples. Abstract : Described is a new approach to building a microfluidic quantum dot wavelength-ratiometric sensor system for quantifying copper in water and biological samples. This simple-to-use, low-cost, sensitive analytical method has great utility as an indicator and quantitative tool, and we have applied it here with copper as the target analyte. CdTe quantum dots of two different sizes, emitting green and red light, are utilized as fluorophores. The green dot is used as a constant emitter and is encapsulated in a silica shell. The red dot, which is immobilized on the silica surface, is quenched in the presence of copper. The dual emission of the quantum dot wavelength-ratiometric sensor results in a fluorescence color change from red to green, identified visually, corresponding to the absence or the presence of copper. The wavelength-ratiometric sensor is mixed with microcrystalline cellulose and dropcast on a microfluidic chip, made of poly(methyl methacrylate) and assembled using polycaprolactone. Red and green intensity values from the RGB system are used as analytical signals for the calibration curve. Copper in water samples is quantitatively determined by constructing a Stern–Volmer plot in the range of 1–30 mg L −1 . For serum samples, absolute values of red and green intensity were plotted to mitigate non-linearity in the Stern–Volmer plot. The microfluidic format of this quantum dot wavelength-ratiometric sensor makes rapid, low-cost testing feasible and convenient for copper detection, directly addressing a diagnostic goal.